Advances in stem cell therapy for erectile dysfunction: preclinical evidence and emerging therapeutic approaches - Xiaoliang Fu; Azar Sheikholeslami; Ulanbek Zhanbyrbekuly; Faezeh Davoodi Asl; Nadiar M. Mussin; Hoda Fazaeli; Karim Daniyalov; Nader Tanideh; Nader Tanideh; Nader Tanideh; Mahdi Mahdipour; Mahdi Mahdipour; et al. (Frontiers in Medicine)
The inability to get or sustain an erection strong enough for fulfilling sexual performance is the hallmark of the common disorder known as erectile dysfunction (ED). It mostly affects a significant percentage of men worldwide, particularly those aged 40 to 70. Even though phosphodiesterase type 5 inhibitors (PDEi) and other conventional therapies have demonstrated efficacy, they frequently prove insufficient for patients with underlying medical disorders such as diabetes, Peyronie’s disease, or post-prostatectomy. This review delves into the therapeutic capacity of stem cells for ED, emphasizing the latest clinical and preclinical studies that showcase their efficacy across various models. The review examines diverse sources of stem cells, including adipose-derived stem cells (ADSCs), bone marrow-derived stem cells (BMSCs), and other emerging sources such as urine-derived stem cells (UDSCs). Critical studies are highlighted, particularly those demonstrating the benefits of MSCs in ED models induced by cavernous nerve injury (CNI), diabetes, and other conditions. The review also explores the role of paracrine signaling, with a focus on factors like vascular endothelial growth factor (VEGF), and brain-derived neurotrophic factor (BDNF), which are involved in the regenerative process. Additionally, the capacity of stem cells with genetic modifications and the integration of stem cell therapy with adjunctive treatments such as platelet-rich plasma (PRP) and shock wave therapy are discussed. Overall, this review underscores significant progress in both clinical and preclinical studies on cell therapy for ED, paving the way for future clinical applications and innovative treatment strategies.